2010
DOI: 10.14713/pcsp.v6i4.1046
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolding Case Formulation: The Interplay of Description and Inference

Abstract: Single subject research (SSR) can complement findings from aggregated group data and contribute uniquely toward the goal of generating and generalizing scientific knowledge in psychology. The present study illustrates these assertions with psychotherapy case formulation research. In earlier work my team and I identified and operationalized multiple dimensions of quality in case formulations. These include comprehensiveness, formulation elaboration, precision of language, complexity, coherence, treatment plan e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…Charman (2004) found that clinicians include the word "intuitive" when describing the skills of effective psychotherapists. In my own research, expert case formulators developed higher quality case formulations than non-experts and did so using a mix of cognitive processes involving shortterm, data-near, intuitive leaps as well as more systematic deductive and inductive processes (Eells, 2010;Eells, Lombart, Kendjelic, Turner, & Lucas, 2005;Eells et al, 2011). Further, it is well documented that experts in a variety of skill domains are capable of accurate, insightful and intuitive judgment (Chi, Glaser, & Farr, 1988;Ericsson, Charness, Feltovich, & Hoffman, 2006;Klein, 1998 of expertise, these individuals quickly perceive large meaningful patterns, are faster than novices at performing the skill in question, and quickly solve problems with little error (Chi, 2006).…”
Section: In Defense Of Clinical Judgmentmentioning
confidence: 99%
“…Charman (2004) found that clinicians include the word "intuitive" when describing the skills of effective psychotherapists. In my own research, expert case formulators developed higher quality case formulations than non-experts and did so using a mix of cognitive processes involving shortterm, data-near, intuitive leaps as well as more systematic deductive and inductive processes (Eells, 2010;Eells, Lombart, Kendjelic, Turner, & Lucas, 2005;Eells et al, 2011). Further, it is well documented that experts in a variety of skill domains are capable of accurate, insightful and intuitive judgment (Chi, Glaser, & Farr, 1988;Ericsson, Charness, Feltovich, & Hoffman, 2006;Klein, 1998 of expertise, these individuals quickly perceive large meaningful patterns, are faster than novices at performing the skill in question, and quickly solve problems with little error (Chi, 2006).…”
Section: In Defense Of Clinical Judgmentmentioning
confidence: 99%
“…Two papers, respectively authored by Eells (2010) and Edwards (2010), explore important aspects of psychotherapy: case formulation competencies and clinician responsiveness within the context of manualized treatments. Additionally, each paper reflects on the unique contribution of idiographic/qualitative methods in furthering our understanding of these complex phenomena.…”
Section: Overviewmentioning
confidence: 99%
“…
ABSTRACTIn this paper two research studies by Eells (2010) and Edwards (2010) evaluating case formulation and therapist responsiveness are summarized and critically evaluated. The central themes abstracted from these studies are subsequently articulated and integrated with existing research on the philosophical and theoretical competencies, clinical competencies, and quantitative competencies needed for effective case formulation.
…”
mentioning
confidence: 99%
“…There are large similarities between the kind of problems presented to researchers by case formulation, the focus of Eells' (2010) research, and by therapist responsiveness during treatment, the focus of my (Edwards, 2010) contribution to this PCSP issue. In both areas, practitioners engage in complex behaviors that involve moment-to-moment decision making in response to an ongoing flow of data in the form of the behavior of or information provided by the client.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…In both areas, practitioners engage in complex behaviors that involve moment-to-moment decision making in response to an ongoing flow of data in the form of the behavior of or information provided by the client. In assessment and case formulation, which Eells examines, the focus is on gathering information in order to develop an understanding of the client's problems in terms of their severity, developmental history, precipitants, and current maintaining factors, a process aptly summarized in Figure 8 of Eells' (2010) article. In my contribution to this PCSP issue, the focus is on the treatment phase of posttraumatic stress disorder (PTSD) and the challenge of: implementing a treatment plan while at the same time building and safeguarding the working relationship with the client; reinforcing and enhancing the client's motivation; tailoring the treatment to the contextual aspects of the client's life; and being alert for new information that might call for revision of the formulation and treatment plan.…”
Section: ____________________________________________________________mentioning
confidence: 99%